2014
DOI: 10.1007/s10620-014-3055-0
|View full text |Cite
|
Sign up to set email alerts
|

The Prophylactic Placement of Hemoclips to Prevent Delayed Post-polypectomy Bleeding: An Unnecessary Practice? A Case Control Study

Abstract: We found no significant difference in the rate of delayed PPB between patients who had prophylactic hemoclipping of polypectomy sites and a well-matched control group of patients who had polypectomy without prophylactic hemoclipping. These data call into question the expensive practice of prophylactic hemoclipping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 13 publications
2
44
0
Order By: Relevance
“…[99][100][101] One RCT of post-EMR defect closure by endoclips compared to no intervention failed to demonstrate any significant benefit. 101 The study was however under-powered for this outcome.…”
Section: Endoscopic Mucosal Resectionmentioning
confidence: 99%
“…[99][100][101] One RCT of post-EMR defect closure by endoclips compared to no intervention failed to demonstrate any significant benefit. 101 The study was however under-powered for this outcome.…”
Section: Endoscopic Mucosal Resectionmentioning
confidence: 99%
“…The hemoclip placement can be requested immediately after polyp resection [21,22] ; in one of our cases hemoclip was used to avoid a post polypectomy complication due to a large tearing of small bowel mucosa. No bleeding and surgical complications have been reported after SBE procedure in our patients.…”
mentioning
confidence: 99%
“…Despite two papers demonstrating a significant benefit in reducing DPPB after prophylactic clipping, there was no significant difference in DPPB when an overall random effect model was applied (odd ratio: 0.8; 95% CI: 0.36–1.77; P = 0.56). Six studies reported 3121 polyps <20 mm and 766 polyps ≥20 mm . However, prophylactic clippings based on polyp size did not result in any overall significant benefit in DPPB reduction (for polyps <20 mm: odd ratio: 1.16; 95% CI: 0.7–1.92; P = 0.56 and for polyps >20 mm: odd ratio: 0.73; 95% CI: 0.08–7.04; P = 0.79) (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Seventy‐two full‐text articles were further assessed. Of these, six were considered eligible for inclusion . The earliest study included was published in 2002.…”
Section: Resultsmentioning
confidence: 99%